APLIKASI DETEKSI PSIKOLOGI ANAK USIA 12 – 15 TAHUN DI SMP BETHEL TASIKMALAYA - Nugraha, Agus Ramdhani (JUTEKIN (Jurnal Teknik Informatika), 2013)
In this era when everything is expected to be instant, especially in field of Information Technology (IT), people are trying to find the quickest and easiest way to get the best solution, for examples are analysis, data processing, etc. Therefore, the progress of computer technology and its development should be able to meet the needs of everyone. It includes the possibility to detect the psychology of an individual. That is why the making of "Application Detection of Children aged 12-15 at SMP BETHEL Tasikmalaya" with the system which the author proposes is expected to help the performance of the ongoing system. The author proposes web-based computerized system. With this web-based computerized system, the data processing will be more effective and the information can be quickly delivered.This application is an application that can detect and find a solution for the psychology of children aged 12-15, which related to their academic and non-academic activities.Keyword : Detection, Children, SolutionÂ